MEANS OF EMOTIVES’ INTENSIFICATION - Kulchytska, Olena (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2023)
The article is devoted to the study of linguistic means of realizing pejoration in the novels by S. Mayer. The topicality of the study is caused by scholarly necessity and importance of studying pejoration from anthropocentric viewpoint, since this vocabulary is rapidly developing and requires analysis and research from different positions. Moreover, the emotive component and the evaluative category in pejoratives have been insufficiently studied. The following definition of pejoratives has been put forward: they are lexemes that have negative, emotionally loaded expressive evaluation and create preconditions for the achievement of an illocutionary goal. They belong to the low style, have a synonym in neutral vocabulary register, have denotative and connotative components of meaning, are prone to change the sign of evaluation, in terms of hybrid semantics have both truth-conditional and use-conditional components and are contextually preconditioned. Vocabulary, the pejorative meaning of which is denotatively registered in lexicographic sources is determined as absolute. Pejoratives, whose meaning is not lexicographically registered, are classified as relative. Semantic field of pejorative vocabulary corpus consists of the nucleus, close and distant periphery. All means of distant periphery serve as intensifiers of pejorative meaning. On the semantic level pejoratives may function as a metaphor, epithet, oxymoron, hyperbole, litote, metonymy, simile, irony and sarcasm. On the syntactic level pejorative vocabulary is integrated into interrogative constructions, inversions, syntactic reductions, stylistic repetitions, antithesis, and word-play. The degree of expressiveness of pejorative meaning has been estimated by means of Likert scale, and it includes the following items: punctuation, semantic and stylistic means, syntactic and stylistic means, graphic symbols, nonce-words and adj/adv + n structure. Pragmatic analysis has yielded the following result: pejoratives are potentially manipulative linguistic means. ______________________ References • Ivanov, L. Tekst nauchnoj diskussii: dejksis i ocenka (Moskva, NIP "2R", 2003), 206. • Kovalenko, E. «Yazykovaya aktualizaciya pejorativnoj ocenki (na materiale anglijskogo yazyka).» (Diss. kand. filol. nauk, Barnaul, 2006), 189. • Tureckova, I. «Sredstva intensifikacii pejoracii v kontekste.» VIII Mezhdunarodnaya nauchno-prakticheskaya konferenciya «Filologiya i kultorologiya: sovremennye problemy i perspektivy razvitiya» (Orenburg, 2014). • Havryliv, O. Verbale Aggression. Formen und Funktionen am Beispiel des Wienerischen (Frankfurt am Main u. a., Peter Lang, 2009): 198. • StephanieMayer. Collection of novels. • Technau, B. The meaning and use of slurs: An account based on empirical data (Amsterdam; Philadelphia, John Benjamins Publishing Company, 2016): 204–298.